Analisis Kinerja Pegawai Pada Bagian Keuangan Sekretariat Kpu Kota Ambon - Silawane, Naifa Nabila; Rengifurwarin, Zainal Abidin; Ponto, Iriane Sosiawaty; Patty, Julia Theresia (Penerbit Goodwood, 2024)
Purpose: This study aims to identify and analyze the factors contributing to the decline in employee performance within the Finance Division of the Secretariat of the General Election Commission (KPU) of Ambon City.. Methodology/Approach: A qualitative descriptive method was employed, with data collected through interviews, observations, and document analysis. The Finance Division of the KPU Secretariat in Ambon City was selected due to the researcher’s internship experience, which facilitated access and contextual understanding. Results/Findings: Employees exhibit strong job knowledge, regulatory adaptability, and professional conduct. However, heavy workloads occasionally lead to delays. Despite this, accuracy and regulatory compliance remain high. Ongoing efforts are focused on enhancing interdepartmental coordination and administrative efficiency. Conclusions: Staff in the finance, general, and logistics divisions demonstrate dedication, flexibility, and awareness of work-life balance. They are continuously improving their skills to better support the operations of the KPU Secretariat in Ambon. Limitations: The study is limited to the Finance Division of the KPU Secretariat in Ambon City and may not fully represent other divisions or locations. Additionally, the qualitative nature of the data may limit broader generalization. Contribution: This research offers insights into employee performance management in public sector institutions, particularly those related to electoral processes. It contributes to human resource management literature and provides recommendations for enhancing employee well-being and operational efficiency in government agencies.